Construction and Validation of Two Hepatocellular Carcinoma-Progression Prognostic Scores Based on Gene Set Variation Analysis - He, Qifan; Fan, Baorui; Du, Peng; Jin, Yonghai (Frontiers in Cell and Developmental Biology, 2022)
Methods: Based on variation of gene expression patterns in different stages, the LIHC-development genes (LDGs) were identified by differential expression analysis. Then, prognosis-related LDGs were screen out to construct the LIHC-unfavorable gene set (LUGs) and LIHC-favorable gene set (LFGs). Gene set variation analysis (GSVA) was conducted to build prognostic scoring models based on the LUGs and LFGs. ROC curve analysis and univariate and multivariate Cox regression analysis were carried out to verify the diagnostic and prognostic utility of the two GSVA scores in two independent datasets. Additionally, the key LCGs were identified by the intersection analysis of the PPI network and univariate Cox regression and further evaluated their performance in expression level and prognosis prediction. Single sample GSEA (ssGSEA) was performed to understand the correlation between the two GSVA enrichment scores and immune activity. Result: With the development of LIHC, 83 LDGs were gradually up-regulated and 247 LDGs were gradually down-regulated. Combining with LIHC survival analysis, 31 LUGs and 32 LFGs were identified and used to establish the LIHC-unfavorable GSVA score (LUG score) and LIHC-favorable GSVA score (LFG score). ROC curve analysis and univariate/multivariate Cox regression analysis suggested the LUG score and LFG score could be great indicators for the early diagnosis and prognosis prediction. Four genes (ESR1, EHHADH, CYP3A4 and ACADL) were considered as the key LCGs and closely related to good prognosis. The frequency of TP53 mutation and Copy number variation (CNV) were high in some LCGs. Low-LFG score patients have active metabolic activity and a more robust immune response. The high-LFG score patients characterized immune activation with the higher infiltration abundance of type I T helper cells, DC, Eosinophils and Neutrophils. While, the high-LUG score patients characterized immunosuppression with the higher infiltration abundance of type II T helper cells, TRegs and iDC. The high- and low-LFG score groups differed significantly in Immunotherapy response scores, immune checkpoints expression and IC50 values of common drugs. Conclusion: Overall, the LIHC-progression characteristic genes can be great diagnostic and prognostic signatures and the two GSVA score systems may become promising indices for guiding the tumor treatment of LIHC patients.